Kajian kesiapsiagaan bencana alam pada masyarakat di desa waiwerang kecamatan adonara timur - Dwi Julia Lanu; Christina Roni Nayoan; Indriati tedju hinga (Jurnal Keperawatan Muhammadiyah, 2023)
The flood and landslide disasters that occurred in Waiwerang Village resulted in many houses being damaged, causing casualties, and many people losing their property. The magnitude of the loss experienced by the community is due to a lack of knowledge about disaster preparedness. Disaster preparedness has a relatively important role, because it relates to the community's ability to act when a disaster occurs. This study aims to determine the community's preparedness in Waiwerang Village, Adonara Timur District for the coming of disasters. This type of research is descriptive quantitative, using survey research. The population in this study were 327 households, with a total sample of 77. The survey results showed that the level of knowledge was in the medium category (63.63%), the emergency response was in the medium category (44.15%), the readiness level was in the not ready category (59.74). %), and empowerment is in the low category (70.12%). The conclusion from this research is that there is a need for disaster preparedness education for the community in Waiwerang Village. Suggestions from this study are that the government can work together with the health office or puskesmas to carry out socialization at schools and in the community such as distributing leaflets, putting up posters or holding training related to disaster preparedness.